Current emerging techniques to impart flame retardancy to fabrics: An overview - Alongi, Jenny; Carosio, Federico; Malucelli, Giulio (Polymer degradation and stability, 2014)
The present paper is aimed to review the state of the art on the novel and emerging techniques recently developed in the textile field for conferring flame retardant properties to natural and synthetic fibres. In particular, a comprehensive description of the results achieved by depositing (nano)coatings on the fabric surface through nanoparticle adsorption, layer by layer assembly, sol–gel and dual-cure processes, or plasma deposition is presented. Finally, the unexpected and recently achieved results in the use of proteins and nucleic acids are discussed.